Similar temperature scale for valence changes in Kondo lattices with different Kondo temperatures - K. Kummer (Nature Portfolio, 2018)
The competition between interactions promoting magnetic order and those suppressing magnetism causes unusual electronic behaviour in Kondo lattice materials. Here, the authors show the energy scale for valence fluctuations is not controlled by the Kondo scale, contrary to expectations from single-site models.